Landscape evolution and deduction of surface deformation in the Soan Dun, NW Himalaya, India. (25th February 2019) - Kothyari, Girish Ch; Joshi, Neha; Taloor, Ajay Kumar; Kandregula, Raj Sunil; Kotlia, Bahadur Singh; Pant, Charu C.; Singh, Rohit Kumar
Abstract: The consequence of strain accumulation along various Himalayan thrusts is manifested in shaping the topography and present day lanscape features of the Himalaya. Consequently, the strain accomodation is attributed to the occurrence of various devastating earthquakes in the Himalayan domain including 1905 Kangra earthquake (Mw 7.8) which occurred along the Kangra valley fault. In the present study, we analyzed and estimatedsss fault related parameters, gradient-length anomaly (GLA) analysis together with Interferometric Synthetic Aperture Radar (In-SAR) measurements to understand the landscape evolution and deformation pattern within the Soan dun (piggy back basin) in the northwest Himalayan front. We combined the results of geodetic, geological, geomorphology and InSAR to constrain the uplift and subsidence between Himalayan Frontal Thrust (HFT) and Main Boundary Thrust (MBT) zones. The estimated results of fault parameters reveal that the horizontal shortening of northwest Himalaya is higher than the vertical uplift. The computed values of GLA magnitude analysis for the uplifted region vary from −9.21 to −0.77, whereas these range from 5.48 to 26.60 for the subsided region. The depicted range of vertical deformation observed from the InSAR measurements ranges from −3.13 to +3.14 mm/y, where the positive and negative value of phases are correlated with the ground uplift and subsidence. The rate of deformation observed from Persistent Scatterer Interferometry (PSI) phase velocity and GLA magnitude is positively supported by the chronologically constrained uplift rates as 3.4 ± 0.3 mm/y. The geomorphic evidences such as folded, tilted and truncated alluvial fan surfaces, offsetting of channels, fault scarps and displaced sedimentary sequences indicate active nature of the Soan dun. The study would be eventually useful for seismic hazard assessment and future infrastructure development in the seismotectonically active regions like Soan dun of NW Himalayan front.